Sebaran Populasi Sapi Friesian Holstein di Beberapa Kabupaten Provinsi Jawa Tengah dan Daerah Istimewa Yogyakarta (Population Distribution of Friesian Holstein Cows in Several Regencies in Middle Java and Yogyakarta Special Province). - Yudi Adinata (Yudi); Sumadi (Sumadi); Adiarto (Adiarto) (Buletin Peternakan, 2009)
The aim of this research was to study the tendency of population distribution of Friesian Holstein (FH) cows and to create a population distribution map of FH cattle in Banyumas, Semarang, Boyolali, and Sleman regencies. Thisresearch was conducted from November 2007 to June 2008. Data collected were those of FH cows population from 2002 to 2006 in Banyumas, Semarang, Boyolali and Sleman Regencies and the production of crosscut grass, field grassand straw from agriculture waste in 2006 in the respective regencies. The result was the model of map of population distribution FH cattle in Banyumas, Semarang, Boyolali and Sleman Regencies. Structure of population of FH cattle inthe year 2006 pursuant to percentage sum up the bull calf, heifer calf, young bull, heifer, bull, cow in Banyumas Regency were 8.25, 13.32, 0.00, 8.86, 0.00, and 69.57%, Semarang Regency were 8.99, 13.00, 7.01, 16.00, 11.00, and44.00%, Boyolali was 9.00, 13.00, 7.00, 16.00, 11.00, and 44.00%, and Sleman Regency were 15.98, 1.58, 20.57, 0.72, and 47.39%. Population growth of FH cattle from 2002 to 2006 in Banyumas, Semarang, Boyolali and Sleman were –4.76, 3.52, 0.93, and 8.99% respectively. The produce of crosscut grass, field grass and straw from agriculture waste pursuant to value of Dry Matter (DM), Crude Protein (CP) and Total Digestible Nutrients (TDN) to requirement ofpursuant to amount of herbivore livestock with Animal Unit (AU) base in 2006 only Banyumas Regency which was still over supply while Semarang, Boyolali, and Sleman Regencies were found insufficient. The dynamics of requirementand availability of DM, CP and TDN from 2007 to 2011 in Banyumas Regency was over supply DM and TDN but insuffiency CP, Semarang Regency was insuffiency DM, CP and TDN, Boyolali Regency was over supply DM but insuffiency CP and TDN, Sleman was over supply DM but insuffiency CP and TDN from 2007 to 2008 and other years insuffiency DM, CP and TDN.